Protein engineering of NADH pyrophosphatase for efficient biocatalytic production of reduced nicotinamide mononucleotide - Liu, Ye; Gong, Jin-Song; Marshall, George; Su, Chang; Hall, Michael; Li, Heng; Xu, Guo-Qiang; Shi, Jin-Song; Xu, Zheng-Hong (Frontiers in Bioengineering and Biotechnology, 2023)
NADH pyrophosphatase, a hydrolase catalyzing the phosphate bond of NADH to reduced nicotinamide mononucleotide (NMNH), has potential applications in the food, cosmetic and pharmaceutical industry. In this study, we describe a NADH pyrophosphatase derived from Escherichia coli (EcNudc). Strategies focusing on expression regulation including screening vectors, optimizing promoters and ribosome binding sites were utilized to enhance the productivity of EcNudc (1.8 U/mL). Moreover, protein engineering was adopted to further improve the catalytic properties of EcNudc, achieving 3.3-fold higher activity and 3.6-fold greater thermostability at 50℃. Furthermore, fermentation for the combined mutant R148A-H149E (EcNudc-M) production in a 7 L fermenter was implemented and the enzyme activity of EcNudc-M reached 33.0 U/mL. Finally, the EcNudc-M was applied in the catalysis of NADH with the highest NMNH yield of 16.65 g/L. Overall, the mutant NADH pyrophosphatase obtained in this paper will lay a foundation for the biocatalytic industrial production of NMNH and expand its application range.